Preliminary Studies of Acid Protease and its Inhibitor in Latex of Hevea brasiliensis - Ampon, Kamaruzaman; Salleh, Maria (1990)
Acid protease (EG 3. 4. 23-) is confined mainly to the bottom fraction of ultracentrifuged Hevea brasiliensis latex. The enzyme has an optimum activity at pH 3.5 and is strongly inhibited by the specific inhibitor, pepstatin. This study reports, for the first time, the presence of a protein inhibitor of the enzyme in the Gserum of Hevea latex.